Clinical Efficacy and Safety of Major Uterine Wall Resection and Reconstruction of the Uterus Combined with LNG-IUS for the Treatment of Severe Adenomyosis - Sun, Cui; Ren, Xiao-yan; Gao, Yi; Liang, Zhi-Gang; Mou, Meng; Gu, Heng-fang; Xiao, Yan-Bing (Geburtshilfe und Frauenheilkunde, 2020)
Objective Aim of the study was to evaluate the clinical efficacy and safety of major uterine wall resection and reconstruction of the uterus (MURU) combined with a levonorgestrel-releasing intrauterine system (LNG-IUS) for the treatment of adenomyosis.Methods Ninety patients diagnosed with adenomyosis were enrolled in this study. All participants were examined by transvaginal ultrasound (TVU) or magnetic resonance imaging (MRI). Serum levels of cancer antigen 125 (CA 125) were quantitatively measured. All patients underwent MURU in combination with LNG-IUS. The therapeutic safety of MURU was assessed during surgery and the patientsʼ stay in hospital. The clinical efficacy was evaluated by comparatively analyzing changes in dysmenorrhea, volume of menstrual blood, uterine volume and serum levels of CA 125 before, and at 3, 6 and 12 months following MURU.Results All 90 patients enrolled in the study were successfully treated with MURU combined with LNG-IUS. No significant complications were observed during surgery and hospital stay. The mean operation time, intraoperative blood loss and length of hospital stay were 82.4 ± 13.8 min, 53.3 ± 20.3 ml, and 4.3 ± 0.8 days, respectively. Dysmenorrhea completely disappeared in all patients. Uterine volume and serum levels of CA 125 were restored to normal ranges. No recurrence of adenomyosis was observed during postoperative follow-up.Conclusion MURU combined with LNG-IUS is an efficacious and safe treatment for severe adenomyosis. This combined technique is not only effective to manage severe adenomyosis but also preserves as much of the uterus as possible.
Keywords: major uterine wall resection and reconstruction of the uterus; levonorgestrel-releasing intrauterine system; adenomyosis; clinical efficacy; safety